Portugal and the enlargement of the European Union - Gaspar, Carlos (2000)
The author situates Portugal's position in the framework of western European development from the post-war period to the present day. He underscores the choice with which the country was faced: the Atlantic or Europe. The current trend suggests a preference for the latter, but the truth is that the choice is not dilemmatic as long as the dual alliance between European and western democracies persists and the institutional duality of the NATO alliance and the European Union lasts.